The Role of BULOG-East Java Regional Division Analysis for Implementing the Absorption of Farmers Agricultural Product in 2015 - Muhamad Rifqi (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2017)
This research analyzes the implementation of rice absorption policy of farmers in 2015 conducted by BULOG. Background of this research, there is an increase of rice production that happened in east java but can not improve farmer's prosperity. BULOG as an implementing agency of presidential policy for the purchase of farmers' rice crops, where this perpres determines the purchase price of the government to maintain the welfare of farmers. The purpose of this research is to analyze the implementation of policy of agricultural absorption of paddy farmer 2015 in East Java and To know the role that dilakuakan by BULOG East Java Regional Division in increasing the absorption of agricultural products. This research uses post positivist approach with qualitative method. The results of this study indicate that as a policy operator, BULOG has done an implementation that is still not good and can do improvement which will have a lot of influence on the welfare of farmers. In the absorption of yield from rice farming itself does not reach the target and proclaimed in BULOG purchased is seen dominated through partners BULOG which this much reduce the income of small farmers. The presence of BULOG is also not timely and much information about absorption by BULOG does not reach the farmers.